2014
DOI: 10.1515/prilozi-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Journals in Republic of Macedonia: the Current State

Abstract: Several biomedical journals in the Republic of Macedonia have succeeded in maintaining regular publication over the years, but only a few have a long-standing tradition. In this paper we present the basic characteristics of 18 biomedical journals that have been published without a break in the Republic of Macedonia. Of these, more details are given for 14 journals, a particular emphasis being on the journal Prilozi/Contributions of the Macedonian Academy of Sciences and Arts, Section of Medical Sciences as one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
8
0
4
Order By: Relevance
“…A total of 37 medical journals have been published in R. Macedonia since the Second World War, either in printed or electronic version [28]. Data referring to 14 titles of journals were obtained from COBIB.MK, but unfortunately only six of them are indexed in the Scopus database, which is an unacceptably low inclusion.…”
Section: Ranking Researchers In the Republic Of Macedoniamentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 37 medical journals have been published in R. Macedonia since the Second World War, either in printed or electronic version [28]. Data referring to 14 titles of journals were obtained from COBIB.MK, but unfortunately only six of them are indexed in the Scopus database, which is an unacceptably low inclusion.…”
Section: Ranking Researchers In the Republic Of Macedoniamentioning
confidence: 99%
“…It was concluded that our medical journals should become a school on how medical problems are treated and how to prepare a paper for medical journals. However, the authors concluded that it is necessary to reach the European level of basic and clinical research in medical science in R. Macedonia [28].…”
Section: Ranking Researchers In the Republic Of Macedoniamentioning
confidence: 99%
“…Medical journals published in the Republic of Macedonia since the Second World War were analysed in an earlier study [4]. A total of 37 journals, either in printed or electronic version, were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that our medical journals should become a school on how medical problems are treated and how to prepare a paper for medical journals. However, the authors concluded that it is necessary to reach the European level of basic and clinical research in medical science in the Republic of Macedonia [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation